The Persistence of Global Masculinism Discourse, Gender and Neo-Colonial Re-Articulations of Violence - Nicholas, Lucy (Springer International Publishing, 2018)
'Surrounded as we are by a masculinized populism that continues to enable insecurity, violence, and oppression, this book demonstrates the depth and breadth of the lineages that facilitate these masculinist practices.' - Brent J. Steele, University of Utah, USA 'This book shows how reactionary movements systematically mobilize masculine resentment, and how that links up with broader structures of patriarchy, white supremacy, and colonialism. It is essential for scholars, writers and journalists seeking to fully understand antifeminism as a political and ideological force.' - Jason Wilson, Columnist and Journalist at The Guardian This book examines whether we are witnessing the resilience, persistence and adaptation of masculinist discourses and practices at both domestic and international levels in the contemporary global context. Beginning with an innovative conceptualisation of masculinism, the book draws on interdisciplinary work to analyse its contours and practices across four case studies. From the anti-feminist backlash that can be found in various men's rights movements, and responses to gender-based and sexual violence, to the masculinist underpinnings of human rights discourse, and modes of intervention to protect, including drone warfare. This interdisciplinary work will appeal to students and scholars of gender studies, security and international relations, and sociology. Lucy Nicholas is Senior Lecturer in Sociology at Swinburne University, Australia. Christine Agius is Senior Lecturer in Politics and International Relations at Swinburne University, Australia. .